Sustanaibility Strategy Management in Affecting Decisions for Purchase of Vehicles Through Leasing Shariah in Indonesia - Pertiwi Utami (AL-FALAH : Journal of Islamic Economics, 2020)
Purpose: Public interest in the purchase of two-wheeled vehicles is very high. With relatively affordable product prices and a variety of applications, financing services facilitate access to vehicle ownership. The majority of consumers choose to use leasing conventional compared to Leasing Sharia. Why does this happen ?, how to attract consumers to be interested in using Leasing Sharia services.Design Methods: This study uses a literature review of interest management strategies and product prices that can be implemented against Sharia leasing to improve decision making for buying motorbikes (two-wheeled vehicles). The sharia economic approach is used as the main reference in expressing good corporate governance.Findings: The findings reveal that the application of efficiency, innovation and fintech sharia efforts is needed to increase consumer interest in vehicle purchase decision making through leasing sharia in IndonesiaOriginalty Value: Efficiency, innovation, and fintech technology based on sharia economic principles in management strategies are urgently needed, seeing the competition of the automotive industry is quite tight in Indonesia.